Characteristics, practices, and outcomes in a Belgian cohort of incident home hemodialysis patients: A 6‐year experience. Issue 3 (19th April 2022) - Vô, Bernard; Anthonissen, Blaise; Verger, Christian; Jadoul, Michel; Morelle, Johann; Goffin, Eric
Abstract: Background: Home hemodialysis (HHD) remains underused in patients with kidney failure. Current literature on HHD mostly originates from non‐European countries, making generalization difficult. The present study describes patients' profile and practice patterns from a Belgian HHD center, and assesses patient and technique survival and complications associated with HHD. Methods: We analyzed data from all our incident patients during a 6‐year period. The patient's characteristics were summarized using descriptive statistics. Transition to another therapeutic modality, estimated using a risk model with death and transplantation as competing events, episodes of respite cares and hospitalizations, and access complications were analyzed. Results: Eighty patients (mean age: 47 years; male: 64%) met the inclusion criteria. Fifty‐one percent of patients initiated dialysis with a central venous catheter (CVC) and 96% were not assisted. Arterio‐venous fistula (AVF) cannulation was performed using buttonhole technique. Standard‐frequent HD (47%) and short‐frequent low‐flow dialysate HD (34%) were mostly used at HHD initiation. Cumulative incidences of technique failure and death were 15%, 24%, and 32% at 1, 2, and 5 years. Incidence rates for respite dialysis and hospitalizations were 2.39 and 0.54 per patient‐year of HHD. In comparison with AVF, incidence rate ratios of overall access complications and access‐related infections for CVC were 4.3 (95% CI: 3.1–6, p  < 0.01) and 4.4 (95% CI: 2.1–10, p  < 0.01), respectively. Buttonhole cannulation was complicated by 0.26 (95% CI: 0.15–0.46) infections per 1000 AVF‐days. Conclusions: This present study provides important information about patient's profile and practice patterns and safety in a cohort of 80 incident Belgian HHD patients, with encouraging techniques and patient survival.